Electric current based power line communication for plug-load device auto identification - Ikegami, Hiroyuki; Tsukada, Manabu; Ochiai, Hideya; Nii, Hideaki; Esaki, Hiroshi (SmartGridComm : 2015 IEEE International Conference on Smart Grid Communications : 2-5 November 2015, 2015)
A smart building has an outlet-level power meters for managing the energy consumption of plug-load devices - the devices or appliances connected to the outlets. Identification of the connected devices used to be made by system operators in the traditional building energy management systems (BEMS), but it is no more realistic for such fine-grained power monitoring applications. This paper proposes a new communication method - electric current based power line communication (ECPLC), which enables automatic identification of plug-load devices without the intervention of system operators. Using ECPLC, a device transmits bit sequences that show its identifier on the electric current flow, which propagates only to the outlet from the connected device. We have designed a transmitter and a receiver of ECPLC with studying the electric model that enables the communication. We have also implemented them, and carried out experiments on varieties of cases. The results show that ECPLC performs very well in typical application scenarios, indicating that it is useful for automatic identification of plug-load devices.